Cover Image, Volume 70, Issue 10. Issue 10 (14th August 2022) - Suo, Na; He, Bingqing; Cui, Shihao; Yang, Ying; Wang, Min; Yuan, Qianting; Xie, Xin
Abstract : Cover Illustration: Invert images from electron microscopy examination of the ultrastructure of myelin sheath in the corpus callosum region of the WT (upper) and GPR149 knockout (lower) mice two weeks after cuprizone withdrawal. GPR149 deficiency results in significantly enhanced remyelination. (See Suo, N. et al, https://doi.org/10.1002/glia.24233 )